The temporo-parietal junction contributes to global gestalt perception—evidence from studies in chess experts - Rennig, Johannes; Bilalic, Merim; Huberle, Elisabeth; Karnath, Hans-Otto; Himmelbach, Marc (Frontiers in Human Neuroscience, 2013)
In a recent neuroimaging study the comparison of intact versus disturbed perception of global gestalt indicated a significant role of the temporo-parietal junction (TPJ) in the intact perception of global gestalt (Huberle and Karnath, 2012). This location corresponded well with the areas known to be damaged or impaired in patients with simultanagnosia after stroke or due to neurodegenerative diseases. It was concluded that the TPJ plays an important role in the integration of individual items to a holistic percept. Thus, increased BOLD signals should be found in this region whenever a task calls for the integration of multiple visual items. Behavioral experiments in chess experts suggested that their superior skills in comparison to chess novices are partly based on fast holistic processing of chess positions with multiple pieces. We thus analyzed BOLD data from four fMRI studies that compared chess experts with chess novices during the presentation of complex chess-related visual stimuli (Bilalić et al., 2011a, 2010, 2011b, 2012). Three regions of interests were defined by significant TPJ clusters in the abovementioned study of global gestalt perception (Huberle and Karnath, 2012) and BOLD signal amplitudes in these regions were compared between chess experts and novices. These cross-paradigm ROI analyses revealed higher signals at the TPJ in chess experts in comparison to novices during presentations of complex chess positions. This difference was consistent across the different tasks in five independent experiments. Our results confirm the assumption that the TPJ region identified in previous work on global gestalt perception plays an important role in the processing of complex visual stimulus configurations.